Academic success: the role of mental toughness in predicting and creating success. Issue 1 (1st January 2018) - Stock, Rosemary; Lynam, Siobhan; Cachia, Moira
ABSTRACT: Research examining the links between Mental Toughness, Positive and Negative Affect and Academic Success was presented at the Annual Higher Education STEM Conference (HEA STEM). The results indicated that undergraduate students of psychology (n = 141) showed a positive correlation between Control of Life (a component of Mental Toughness) and Academic Success, as measured by their grades. Further relationships between components of each scale were found to differ between genders. Females showed negative relationships between Confidence in Abilities and Control of Emotion and Academic Success, while males showed links only between Commitment and Positive Affect, and Commitment and Academic Success – both of these being positive relationships. In this conference reflection piece, the results of this research will be examined in the light of the wider discussions on employability in relation to 'Resilience' and how Academic Success is measured.